Pengaruh Literasi, Pengelolaan, dan Inklusi Keuangan Terhadap Kinerja Keuangan Umkm Digital Printing di Ponorogo - Arifai, Abdul Azis; Rapini, Titi; Wahyuningsih, Dwi Warni (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2024)
This study explores the understanding of personal finance, management, and access to financial services impact the performance of 31 digital printing SMEs in Ponorogo. Thirty business owners were surveyed, and the data was examined using regression. The findings show that financial literacy and management do not significantly affect performance, but financial inclusion does. The F-test confirms that all three factors together influence the businesses' financial performance. Keywords: Financial Literacy, Financial Management, Financial Inclusion, and Financial Performance